2005
DOI: 10.1111/j.1420-9101.2004.00821.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of constraints: the contributions of selection and genetic variance to the maintenance of cotyledon number in wild radish

Abstract: The evolutionary mechanisms underlying the maintenance of invariant traits are poorly understood, partly because the lack of variance makes these mechanisms difficult to study. Although the number of cotyledons that plant species produce is highly canalized, populations of plants frequently contain individuals with abnormal cotyledon numbers. In a garden study with 1857 wild radish plants from 75 paternal half‐sibling families, 89 (almost 5%) had cotyledon numbers less or greater than two. We found evidence fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 33 publications
(46 reference statements)
2
20
0
Order By: Relevance
“…The present study discuss canalization of cotyledon number and bifurcation or lobbing as cause of more than two cotyledons formation (Conner and Agrawal, 2005;Chandler, 2008).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The present study discuss canalization of cotyledon number and bifurcation or lobbing as cause of more than two cotyledons formation (Conner and Agrawal, 2005;Chandler, 2008).…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies reported more and less than two cotyledons in the family Aceraceae, Juglandaceae, Rubiaceae, Pedaliaceae, Protaceae, Ranunculaceae, Papaveraceae, Brassicaceae, Fabaceae, Geraniaceae, Chenopodiaceae, Onagraceae, Solanaceae, Scrophulariaceae, Salicaceae and Euphorbiaceae (Gates, 1910;Went, 1944;Harrison, 1964;Dessureaux, 1967;Magsar and Tsagaanmaam, 1984;Rajora and Zsuffa, 1986;Taylor and Mundell, 1999;Graz, 2001;Conner and Agrawal, 2005;Chandler, 2008). The present results show three, four cotyledons and different shape dicotyledons in Peganum genus (Peganaceae), in addition to above mentioned families.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…External such as drought, salinity as well as endogenous factors such as phytohormones, proteins, transcription and other substances can affect embryogenesis (Unnikrishnan et al, 1990;Khorolsuren & Jamsran, 2005;Umehara et al, 2007). Previous studies reported that salinity effects on seed germination and early seedling growth (Rahman & Ungar, 1990;Gulzar et al, 2001;Bayuelo-Jimenez et al, 2002;Jamil et al, 2005Jamil et al, , 2006Lombardi & Lupi, 2006;Cordazzo, 2007;Necajeva & Ievenish, 2008;Bybordi & Tabatabaei, 2009;Sivasankaramoorthy et al, 2010;Akbarimoghaddam et al, 2011), and approved that the formation of three cotyledons is related with embryogenesis (Taylor & Mundell, 1999;Al-Hammadi et al, 2003;Conner & Agrawal, 2005).…”
mentioning
confidence: 98%